Analisis Penerapan Akad Murābahah dalam Perspektif Fikih Muamalah di Koperasi Tamam STIBA Makassar: An Analysis of Murābahah Contract Implementation from Fiqh Muamalah Perspective at Tamam Cooperative STIBA Makassar - Muhammad, Muhammad (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2025)
The study of murābahah contracts is a significant discourse within the discipline of fiqh muamalah, emphasizing the need to ensure that Islamic financial practices comply with the legal pillars and conditions of valid sales. The occurrence of non-compliant practices, such as bay’ mā lā tamlik (selling what is not owned) and bai’atain fi bai’ah wāhidah (two contracts in one sale), necessitates an analysis of their implementation in Islamic microfinance institutions. The research aims to (1) describe the mechanism of murābahah implementation at Tamam Cooperative, and (2) analyze its compliance with classical and contemporary fiqh principles. This is a qualitative case study employing in-depth interviews, document observation, and library research using classical fiqh books, DSN-MUI fatwas, and academic literature. The findings indicate that the cooperative’s murābahah practice generally complies with Sharia principles, especially regarding ownership, transfer of possession (qabd), risk management (ḍamān), and price transparency. A distinctive feature of Tamam Cooperative is its homogeneous membership base (lecturers and campus administrators), which eliminates the need for formal wa’d documents or collateral; instead, moral commitment underpins transactions. This study contributes to the field of Islamic commercial law by offering a case of community-based murābahah practice that is simple yet Sharia-compliant, potentially serving as a model for other Islamic microfinance institutions.